(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate peripheral oxygen saturation after wearing different face masks and related anxiety in healthcare workers amid COVID -19 Pandemic at a tertiary care facility. Study Design: Cross-Sectional, Observational and Comparative Study Place and Duration of Study: This study was conducted at the Isra University Hospital Hyderabad from June 2020 to July 2020. Materials and Methods: The study was done on group of healthcare workers of the tertiary care hospital; sample size was 57. Informed consent was obtained from all enrolled participants. Proforma was designed and filled by each participant. Data was analysed on SPSS version 22. Chi square test was applied for statistical significance. Results: Gender distribution of participants in study population male were 39 (68.4%), female 18 (31.6%). Most common age group was 20 – 40 year (89.5%) age range 22 – 66 year. Peripheral Oxygen Saturation was not affected with wearing different masks in different ventilation areas except poorly ventilated area which was environmental. Anxiety related to wearing masks amid Covid – 19 pandemics was statistically significant < 0.05. Conclusion: It is concluded that there is no effect on peripheral oxygen saturation after wearing different masks in different ventilation areas except poorly ventilated area which was due to environment. There is statistically significant value < 0.05 for related anxiety in healthcare workers after wearing face masks amid COVID - 19 pandemic.